Effect of temperature on the mechanical performance of highly conductive composites for HT-PEMFC application - Teuku Husaini,; Shuhaimi,; Abu Bakar Sulong, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study is a follow-up study of a previous study that examined the effect of temperature on the mechanical performance of the polymer carbon composite (CCP). In this study, the optimal formulation obtained from previous studies, was tried for use in polymer fuel cells of high temperature polymer electrolytes. The standard used is, the standard for bending strength specified by the US Department of Energy (DOE) Agency, which has determined the bending strength should be higher than 25 a. Preparation of CCP bipolar plates is done by internal mixing and then molded by compression stirring method. Bending strength and hardness test are carried out at 26°C to 200°C, for 80% CNT/NG mixture and 20% by weight of EP, with a resin/hardener ratio of 3: 1. This composition has successfully met the bending strength standards set by the DOE on testing performed at room temperature. However, the composite electrical conductivity is still less than the standard set by DOE, reaching only 50 S/cm. The results show that the composite plate of CNT/NG/EP mixed with a 5/75/20% by weight composition is not suitable for HT-PEMFC, because the filler and matrix composite interface failed to hold the bonds at temperature higher than the melting point of the EP. It is therefore recommended that this composite material be used only at low temperatures and is also not recommended for use as a fuel cell plate.